Politics Without Meso-Level? No Politics at the Meso? - Pálné Kovács, Ilona (Frontiers in Political Science, 2021)
The paper examines the role of meso-level governance in the Hungarian political system focusing on the county self-governments but embedded in some theoretical and comparative implications. The objective of the author is to elucidate the theoretical framework of meso-level politics in general and to contrast international models of meso-level political integration with the current situation in Hungary. The paper focusing on Hungarian counties seeks to explore the three-decade-long process leading to the progressive elimination of these bodies from the public power arena.The Hungarian case demonstrates how the overall centralisation process has contributed to the hollowing out of counties as meso-level political actors. The case study underlines the complex interrelations between the party-system, the election model, territorial political and self-governmental arenas and the centre and periphery relations. According to our hypothesis, the weakness or absence of the meso-level is a significant obstacle to strengthening the self-government sector at large since decentralisation will be lacking a very important institutional guarantee, i.e. the meso. The meso is not only a platform for territorial interest representation but also a counterbalance of the central level contributing the quality and stability of democratic governance. Following the review of institutional frameworks of territorial governance in Europe, the paper will analyse the election results and new, informal channels for territorial interest representation in Hungary.